Effect of Dynamic Neuromuscular Stabilization Exercises on Activity of External Oblique Muscle in Low Back Pain - Hediyeh Hosseini; Abbas Rahimi; Khodabakhsh Javanshir; Mohammad Taghipour; Aliyeh Daryabor; Sedigheh Sadat Naimi (Journal of Modern Rehabilitation)
Introduction: Dynamic neuromuscular stabilization (DNS) or core stabilization exercises have been used to improve core stability, but their effect on nonspecific low back pain (NSLBP) is still not fully understood. This study aimed to investigate the effect of DNS exercises on the electromyography (EMG) activity of the external oblique muscle in people with NSLBP. Materials and Methods: In a randomized clinical trial, 44 people with chronic NSLBP were randomly assigned to the experimental and the control groups, with 22 participants in each group. The control group received standard physical therapy exercises, while the experimental group performed DNS exercises. Each group underwent an 8-week therapeutic exercise program, 5 sessions per week, with each session lasting approximately 60 minutes. Surface EMG was utilized to assess the core muscle activity of the external oblique. The EMG activity of the external oblique was measured in both groups before and after the 8-week intervention. Results: Nineteen people in the control group and 21 in the DNS group were analyzed. The results showed that after the intervention, patients in the DNS group obtained, on average, an 8.82% (95% CI, 6.53%, 11.10%) higher increase in the EMG activity of the external oblique muscle compared to the patients in the control group (P<0.001, effect size: 0.622). Conclusion: DNS exercises can be recommended for improving the activation of superficial core muscles like the external oblique in individuals with NSLBP.